2021
DOI: 10.9734/ejnfs/2021/v13i330395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Raw Groundnuts from Makurdi Markets in Nigeria for Aflatoxin B1

Abstract: Aims: The contamination of groundnut by aflatoxins (AF) results in financial losses to farmers’ as well as severe food safety and public health challenges globally. This study was carried out to; (i) assess the levels of AFB1 in husked groundnut seeds in Makurdi (ii) determine the relationship between moisture content and AF levels, and (iii) investigate vendors’ knowledge, attitudes and practices (KAP) of AF and their approach towards groundnut storage. Study Design: Quantitative research method was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…The results are also comparable to those reported from a study conducted in Nigeria (Ityo et al, 2021) which reported a low level of knowledge of aflatoxin among groundnut retailers (<40%). Unlike microbial contaminants, mycotoxins often occur in doses far below those accountable for acute effects but may induce long-term conditions (such as cancer) (Ghazi et al, 2020), cause stunting, and depress immunity (Kimanya et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…The results are also comparable to those reported from a study conducted in Nigeria (Ityo et al, 2021) which reported a low level of knowledge of aflatoxin among groundnut retailers (<40%). Unlike microbial contaminants, mycotoxins often occur in doses far below those accountable for acute effects but may induce long-term conditions (such as cancer) (Ghazi et al, 2020), cause stunting, and depress immunity (Kimanya et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…On a global scale, the agricultural sector faces a notable challenge concerning the increasing value of groundnuts, primarily attributed to the demand for aflatoxin-free produce [1][2][3][4]. Women, who are predominantly involved in the groundnut postharvest value chain, play a crucial role in addressing this challenge [5][6][7].…”
Section: Introductionmentioning
confidence: 99%